HEMORRHAGIC BRAIN LESIONS AS COMPLICATION OF METHANOL INTOXICATION: A CASE REPORT (Journal of Pharmaceutical Negative Results, 2023)
Methanol poisoning could lead to life-threatening comorbidities including fatal brain hemorrhages that its etiology has not been studied enough. Herein a rare case of intracranial and intraventricular hemorrhages was presented in a 32 years old man leading to brain death. Methanol poisoning could initiate coagulopathies and vascular endothelium damage by metabolic acidosis, and toxic effects of its metabolites that beside other risk factors in alcohol abusers like liver disease could lead to fatal hemorrhagic adverse events. Early diagnosis and sufficient therapeutic approaches are essential in reducing mortality and morbidity of this toxicological emergency that implies the importance of available facilities and medications in emergency departments for management of methanol poisoning.